1.
1 (X-1)(X+1)= X的2次方-1
2 (X-1)(X的2次方+X+1)= X的3次方-1
3 (X-1)(X的3次方+X的2次方+X+1)= X的4次方-1
4 (X-1)(X的4次方+X的3次方+X的2次方+X+1)= X的5次方-1
所以(X-1)×(X的N-1次方+X的N-2次方+X的N-3次方+ .+X+1)=X的N次方-1
验证的话要用归纳法.
假设N=k次方成立
则(X-1)×(X的k-2次方+X的k-3次方+ .+X+1)=X的k次方-1
当N=k+1时
(X-1)×(X的k次方+X的k-1次方+X的k-2次方+X的k-3次方+ .+X+1)=(X-1)×(X的k次方)+(X-1)×(X的k-1次方+X的k-2次方+X的k-3次方+ .+X+1)=(X-1)×(X的k次方)+(X的k次方-1)=X的(k+1)次方-1
所以成立
2.
设1.345=A,0.345=A-1,2.69=2A
原式=A(A-1)*2A-A^3-A(A-1)^2
=A[2A(A-1)-A^2-(A-1)^2]
=A[2A^2-2A-A^2-A^2+2A-1]
=A(-1)=-A=-1.345
3.
分析:该题的出题目的是为了比较(2m+3)(2m-3)+12m与(2m+3)^2的大小.故可用作差法比较.解法如下:
(2m+3)(2m-3)+12m-(2m+3)^2=(4m^2-9+12m)-(4m^2+12m+9)=-18